BACTERIOLOGICAL INVESTIGATION OF PRAWN CANNERIES II. INCIDENCE OF CLOSTRIDIUM PERFRIDGENS - NAMBIAR, V NARAYANAN; IYER, K MAHADEVA (Fishery Technology, 2016)
Prawn processing factories of the three major fish processing centres of the West Coast of India, viz., Cochin, Mangalore and Calicut were surveyed to determine the occurrence of Clostridium perfringens in processing areas, and in processed products. Direct plating on Sulphite -polymyxin- sulphadiazine Agar and enrichment techniques were used. Samples of prawn, prawn guts, frozen prawns, canned prawns, water, ice, swab from utensils and soil from the factory premises were examined. Among a total of 461 samples examined, only 32 (6.9%) gave positive results. The incidence of C. pe1jringens was more in prawn guts (80%), followed by soil (50%), prawn (38%), ice (33.3%), frozen prawns (11%), swab (5.0%) and water (1.1%). No C. perfringens was isolated from canned prawns.